Critical role of the neutrophil-associated high-affinity receptor for IgE in the pathogenesis of experimental cerebral malaria - Porcherie, Adeline (The Rockefeller University Press, 2011)
The role of the IgE–FcεRI complex in malaria severity in Plasmodium falciparum–hosting patients is unknown. We demonstrate that mice genetically deficient for the high-affinity receptor for IgE (FcεRIα-KO) or for IgE (IgE-KO) are less susceptible to experimental cerebral malaria (ECM) after infection with Plasmodium berghei (PbANKA). Mast cells and basophils, which are the classical IgE-expressing effector cells, are not involved in disease as mast cell–deficient and basophil-depleted mice developed a disease similar to wild-type mice. However, we show the emergence of an FcεRI(+) neutrophil population, which is not observed in mice hosting a non–ECM-inducing PbNK65 parasite strain. Depletion of this FcεRI(+) neutrophil population prevents ECM, whereas transfer of this population into FcεRIα-KO mice restores ECM susceptibility. FcεRI(+) neutrophils preferentially home to the brain and induce elevated levels of proinflammatory cytokines. These data define a new pathogenic mechanism of ECM and implicate an FcεRI-expressing neutrophil subpopulation in malaria disease severity.